Evaluation of The Objective Criminal Policy of Law No. (6) Of 2024 Regarding The Criminalization of Witchcraft, Sorcery, Divination and its equivalents (Al-Mukhtar Journal of Legal Science, 2025)
This study provides a critical assessment of Libyan Law No. (6) of 2024 criminalizing witchcraft, suggesting it needs serious review. The study demonstrates the ambiguity of the protected legal interest, the text's lack of precise definitions of the terms "witchcraft," "sorcery," and "divination," its failure to differentiate between gratuitous and profitable activities. Nevertheless, the study acknowledges some positive aspects of the legislation, including the criminalization of preparatory acts, attempts to dry up the sources of crime, and strengthen the protection of religious and social values. It concludes that a comprehensive reformulation of the law is necessary, graduated and humane penalties, and judicial review mechanisms to achieve a sound balance between protecting public order and safeguarding fundamental rights and freedoms.
Keywords: Witchcraft; Sorcery; Divination; Self-Interest; Criminalization; Punishment